The multi-layered-ness of urban segregation: On the simultaneous inclusion and exclusion in Latin American cities. (May 2016) - Smets, Peer; Salman, Ton
Abstract: Although segregation is a worldwide phenomenon, this paper will focus mainly on Latin American urban areas. We will discuss approaches – rooted in e.g. geography, economics, sociology, and anthropology – for measuring, analysing and describing segregation patterns at places of residence, workplaces, recreation and shopping areas, in political participation and access to justice, and others. In doing so, we will also address different quantitative and qualitative theoretical approximations and methods of research to unpack these different segregation manifestations. We will illustrate this by giving examples of different kinds of socio-cultural, economic, financial, political and judicial inclusion and exclusion. In short, this paper provides an overview of different kinds and types of segregation and their mutual relationships, ranging from reciprocal strengthening to surprising combinations to clear-cut contradictions, to contestations.